ANALYSIS OF DYSPHEMIC LANGUAGE IN PRE-SCHOOL AGED CHILDREN CASE STUDY: SALSA APRILIA PUTRI (SEMANTIC STUDY) - Dewi Wulan Sartika (PIKTORIAL : Journal of Humanities, 2023)
Dewi Wulan Sartika. NIM: 181010700062. Analysis of Language Dysphemia inPre-School Age Children Case Study: Salsa Aprilia Putri (Semantic Study).Essay. Indonesian Literature Study Program, Faculty of Letters, University Pamulang. South Tangerang. 2023. Thesis research on Language Analysis of Dysphemia in Pre-School Age Children Case: Salsa Aprilia Putri (Semantic Study), aims to make contribution in the treasures of linguistic research, especially semantics. Besides that this study aims to: 1). Describe the form of language use dysfemia acquired by Salsa Aprilia Putri. 2). Describe the meaning of language curse uttered by Salsa Aprilia Putri. This research uses qualitative descriptive research. The object in this study is a child aged pre-school named Salsa Aprilia Putri. The data in this study taken from the language spoken by Salsa Aprilia Putri in everyday life day. Data collection was carried out by observing and noting techniques. This research using the theory of Dysphemia language in Lexicology and Lexicography Books by Abdul Chaer and using the cursed language theory of Timothy Jay. Results From this study, there are 28 sentences containing dysfemia language finally from the analysis of the acquisition of results there are 27 forms of word dysphemia, 6 forms phrase dysfemia and 7 forms of clause dysfemia uttered by Salsa Aprilia Putri.Keywords: Dysphemia, Semantics, linguistics